The experience of nursing students of clinical teaching: The impact of clinical experience of instructors - Zareei, farzaneh; Abed Saeedi, zhila; Shahoei, ronak (Advances in Nursing & Midwifery, 2015)
Abstract Background and aim: Despite the recognition of the clinical instructor impact on quality of nursing students'learning, recent research indicate many problems in nursing instructors' performance. Many factors contribute to effective clinical teaching and the instructors' clinical experience may affect their teaching quality. The aim of this study was to explore student nurses' experiences regarding their clinical teachers' experiences in nursing practice . Method and materials: A qualitative approach was used for the study. The study protocol was approved by research committee of the school of medical education. A purposive sample of undergraduate nursing students at their internship placements participated in the study. Data were collected by semi structured interviews. Interviews were recorded and transcribed verbatim. A conventional content analysis approach was used for data analysis. Data saturation was reached by 12th interview . Results: After coding and clustering the data 6 themes emerged. These themes were as below: 1- peace of mind 2- getting interested in nursing 3- effective clinical learning (impact of working with an instructor who has clinical experience) and 4-anxiety 5-no interest in nursing 6- ineffective clinical teaching ( working with instructors without any clinical experience). Conclusion: The clinical background and nursing skills of clinical teachers is a major factor for effective teaching in clinicalsettings.